2005
DOI: 10.1007/s00216-005-3178-4
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatographic/mass spectrometric investigation on the reaction products in the peroxidase-catalyzed oxidation of o-phenylenediamine by hydrogen peroxide

Abstract: Mass spectrometric evidence was obtained to confirm that the main reaction product of the horseradish peroxidase (POD)-catalyzed oxidation of o-phenylenediamine (OPD) by hydrogen peroxide is 2,3-diaminophenazine. Although this reaction is one of the most widespread detection schemes in enzyme-linked immunosorbent assays (ELISAs), the literature data on the identity of the reaction product(s) have been strongly contradictory throughout the last few decades. Liquid chromatography with UV/Vis and mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…This finding was open to discussion during the following several decades until Tarcha et al (1987) obtained indisputable NMR and mass spectroscopic evidence which indicated that the major product of the oxidation of o -PDA by H 2 O 2 or HRP/H 2 O 2 is DAP. Liquid chromatography combined with UV/Vis, IR, 2-D NMR, and MS has also led to the unambiguous detection of DAP as a major reaction product of the HRP-catalyzed oxidation of o -PDA with H 2 O 2 , whereas 2,2′-diaminoazobenzene, which was suggested by other researchers (e.g., Gallati and Brodbeck 1982) to be the major reaction product, was not detected (Hempen et al 2005). Because of this reaction, o -PDA became one of the most effective substrates for spectrophotometric HRP-mediated enzyme-linked immunosorbent assay (ELISA test) that uses antibodies and color change to identify a substance (Wolters et al 1976; Bovaird et al 1982; Mekler and Bystryak 1992).…”
Section: Enzymatic Oligomerization Of Arylaminesmentioning
confidence: 98%
“…This finding was open to discussion during the following several decades until Tarcha et al (1987) obtained indisputable NMR and mass spectroscopic evidence which indicated that the major product of the oxidation of o -PDA by H 2 O 2 or HRP/H 2 O 2 is DAP. Liquid chromatography combined with UV/Vis, IR, 2-D NMR, and MS has also led to the unambiguous detection of DAP as a major reaction product of the HRP-catalyzed oxidation of o -PDA with H 2 O 2 , whereas 2,2′-diaminoazobenzene, which was suggested by other researchers (e.g., Gallati and Brodbeck 1982) to be the major reaction product, was not detected (Hempen et al 2005). Because of this reaction, o -PDA became one of the most effective substrates for spectrophotometric HRP-mediated enzyme-linked immunosorbent assay (ELISA test) that uses antibodies and color change to identify a substance (Wolters et al 1976; Bovaird et al 1982; Mekler and Bystryak 1992).…”
Section: Enzymatic Oligomerization Of Arylaminesmentioning
confidence: 98%
“…This is in accord with reported data which are obtained from HRP catalyzed formation. The oxidation of o-phenylenediamine via diazo reaction can thus be excluded since the expected product, 2, 2'-diaminoazobenzene [10], exhibits a molecular ion of 212. Therefore, we propose that laccase can also catalyze the monomer, ophenylenediamine, to form free radicals.…”
Section: Resultsmentioning
confidence: 99%
“…However, the structure of this dimer has not been experimentally determined, although it has been suggested to be 2-amino-N-(2-aminophenyl)-pbenzoquinone diimine (AABI) [31] or 5,10-dihydro-2,3-diaminophenazine (DDAP). [32] Here, experimental evidence was found that supports the existence of AABI rather than DDAP. Firstly, in analogy to BQD, this dimer can also form an adduct with BHA ( Figure S1 and Scheme S1 in the Supporting Information), which indicates the existence of a di-A C H T U N G T R E N N U N G imine structure.…”
Section: Resultsmentioning
confidence: 59%